Reduced order modelling applied to augmented reality - Badias, Alberto; Alfaro, Iciar; González, David; Cueto, Elias (Jornada de Jóvenes Investigadores del I3A, 2018)
Augmented reality is one of the fields with greatest interest in technological research. Real time requirements force to use physics engines to approximate the behaviour of the objects. We propose the computation of the proper equations that govern the physics of deformable objects, and their interaction with users in real time, using dimensionality reduction techniques.